Consumer Buying Behavior on Myntra: Analyzing Influencing Factors and Their Impact on Satisfaction - Jadhwani, Om; Mohnia, Tiya; Suda, Pranjal; Chauhan, Rahul; Maseleno, Andino (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research explores consumer buying behavior on Myntra, a leading online fashion platform in India, focusing on factors influencing purchasing decisions and their impact on customer satisfaction. A survey of 100 Myntra users in Ahmedabad was conducted, utilizing a quantitative approach and stratified random sampling. The study identified key factors such as pricing, product variety, promotions, and user experience, and evaluated their role in shaping consumer behavior. The findings suggest that demographic variables (age, gender, and occupation) have minimal influence on shopping behavior, while satisfaction and purchase decision-making were influenced by factors like pricing strategies and personalized recommendations. The study provides insights into Myntra's market positioning and offers recommendations for improving customer engagement.